A RADICAL‐RIGHT POPULIST DEFINITION OF CROSS‐NATIONAL REGIONALISM IN EUROPE: Shaping Power Geometries at the Regional Scale Beyond State Borders. (29th October 2021) - Lamour, Christian
Abstract: Radical‐right populism has become a structural political phenomenon in the European Union in recent years. This ideology, the core principle of which is based on a nurtured antagonism between the 'people' and the 'elite', combined with a parallel promotion of authoritarian and nativist ideas, is generally associated with the nation state and its core territorial ideology: nationalism. However, populism can also be scaled at the regional level, within or across European state borders. This article, which is based on critical discourse analysis, aims to investigate what might constitute the meaning of cross‐national regionalism according to a radical‐right populist leader in Europe. More precisely, my objective is to research the antagonism this type of leader can structure to organize territorial, symbolic and institutional claims associated with a specific cross‐national region. This research is based on the discourse Hungarian Prime Minister Viktor Orbán produced in relation to the Visegrád region. My analysis helps to reveal the types of power geometries articulated by populist leaders beyond state borders.